Religionswissenschaft - Stausberg, Michael (De Gruyter Studium, 2012)
What constitutes the field of religious studies? The 29 chapters in this introductory text offer an incisive look at the key approaches, methods, problems, and subjects that define contemporary academic research in the field of religious studies at universities in the German-speaking world. It provides a unique and polyphonic portrait of contemporary religious studies. The contributions are written in a clear, accessible style; an appendix with supplemental reading aids helps one to navigate the individual contributions